2018
DOI: 10.1111/1759-3441.12235
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Integration Reduce Output Volatility? New Evidence from Cross‐Country Data

Abstract: We examine the effect of financial integration, measured based on both volume and equity, on output volatility using five‐year non‐overlapping annual average data windows for sixty countries over the 1971–2015 period. We construct aggregate‐ as well as sub‐panels based on income and region. Financial integration reduces output volatility in aggregate and income panel, but not in all regions. Foreign direct investment (FDI) and foreign portfolio investment (FPI) reduces output volatility in developed countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In addition, our estimation results reveal that the volatility of the growth rate tends to drop between 0.874 per cent to 4.219 per cent for every 1 per cent increase in financial development (i.e., lnFD t , lnM2 t , lnM3 t , lnPRI t , and lnBC t ). These findings are corroborated with previous studies such as Sahoo et al (2019), Moradbeigi and Law (2016), Ćorić and Pugh (2013), Dabla-Norris and Srivisal 2013, Darrat et al (2005), Denizer et al (2002), Taylor (1994Taylor ( , 1996, Levine (1997), and Bencivenga and Smith (1992). Next, we extend our study to investigate the moderating effect of financial development on the impact of inflation volatility, trade openness and FDI on growth volatility in Malaysia.…”
Section: Methodology and Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, our estimation results reveal that the volatility of the growth rate tends to drop between 0.874 per cent to 4.219 per cent for every 1 per cent increase in financial development (i.e., lnFD t , lnM2 t , lnM3 t , lnPRI t , and lnBC t ). These findings are corroborated with previous studies such as Sahoo et al (2019), Moradbeigi and Law (2016), Ćorić and Pugh (2013), Dabla-Norris and Srivisal 2013, Darrat et al (2005), Denizer et al (2002), Taylor (1994Taylor ( , 1996, Levine (1997), and Bencivenga and Smith (1992). Next, we extend our study to investigate the moderating effect of financial development on the impact of inflation volatility, trade openness and FDI on growth volatility in Malaysia.…”
Section: Methodology and Resultssupporting
confidence: 91%
“…An example of the first strand is the financial accelerator framework engineered by Bernanke et al (1999) and the general equilibrium model of Portes (2007) which claimed that an influx of FDI reduces output volatility because international capital inflows reduce financial constraints for domestic investment which eventually reduces economic volatility. Indeed, the studies of Sahoo et al (2019), and Ćorić and Pugh (2013) also reveal a significant negative relationship between FDI inflows and output volatility in both developed and developing countries. However, the second strand of literature argues that FDI is the cause of high economic fluctuation.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Ang (2011) suggests that increasing financial openness will lead to reduced consumption volatility in India, and Rangvid et al (2016) find that increased capital market integration helps increase consumption risk-sharing. Most recently, Sahoo et al (2019) find a similar reduction in output volatility for a set of 60 countries.…”
Section: Previous Studies Related To Macroeconomic Volatility and Economic Integrationmentioning
confidence: 71%
“…(Kose et al, 2006;Schindler, 2009;Alagidede et al, 2020). From the literature, the studies of FI observed in the case of Asian countries (Park, 2013;Gan, 2014), the Europen Union (Kose et al, 2006;Hoffmann et al, 2020) and also for the global economy (Razin and Rose, 1994;Sahoo et al, 2019). More importantly, FI and growth are linked, as many studies expressed that the more financially integrated countries are signified with higher growth (Easterly et al, 2001;Kose et al, 2003;Friedrich et al, 2013;Cheng and Quang, 2014).…”
Section: Introductionmentioning
confidence: 99%